Hubungan Dukungan Keluarga Anak Stunting Dengan Efikasi Diri Pada Klien Tuberkulosis Multi Drug Resistant - Hilman Mulyana (Jurnal Keperawatan BSI, 2022)
Background: According to the WHO Global Report, Indonesia includes 27 countries with a high burden of MDR-TB because every year there are always MDR-TB cases, one of which is in West Java Province during 2017 there were 28 rifampin-resistant TB patients from 603 suspected MDR-TB patients examined. they have been in the laboratory. In Tasikmalaya City there were 30 patients spread across several Puskesmas areas in 2018, interestingly there are 16 people who have family members with stunting children. It is known that in the city of Tasikmalaya there are 32% stunting children, which is quite high above the standards set by WHO, namely 20% of the total proportion of children under five. Such conditions certainly affect the support provided by the family to the patient. Methods: This type of research is descriptive quantitative, with the independent variable being family support and the dependent variable being the self-efficacy level of MDR-TB clients. The population is 30 respondents of MDR-TB clients, a sample of 16 people with the condition of having family members of stunting children based on inclusion and exclusion criteria and analyzed univariate and bivariate with Spearman rank correlation statistical test. Results: there is no relationship between family support having stunting children with self-efficacy on MDR-TB clients at the Tasikmalaya City Health Center with the Spearman Rank test results obtained a value of = 0.323 (> 0.05). Conclusion: in this case the MDR-TB client does not get maximum support from the family because family members are faced with a situation where there are two problems being faced at the same time. Suggestion: more in-depth research on all the variables that have been studied above by taking a long time to obtain more secondary data and find other confounding factors.